2015
DOI: 10.1007/s00167-015-3541-8
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate sagittal femoral component alignment cannot be ensured by intramedullary alignment rods

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
(53 reference statements)
1
32
0
Order By: Relevance
“…Computernavigated and robotics use technologies such as intraoperative navigation and second calibration to achieve more accurate intramedullary positioning and femoral osteotomy. However, many studies have proven that they are not superior to the conventional method in the femoral component position [16,[42][43][44]47]; PSI also does not provide better results in this field [14,45].…”
Section: Discussionmentioning
confidence: 99%
“…Computernavigated and robotics use technologies such as intraoperative navigation and second calibration to achieve more accurate intramedullary positioning and femoral osteotomy. However, many studies have proven that they are not superior to the conventional method in the femoral component position [16,[42][43][44]47]; PSI also does not provide better results in this field [14,45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is required to restore sagittal alignment of both femoral and tibial components accurately and precisely, which was not easy to be accomplished via conventional techniques. The exion of femoral component was highly varied in conventionally aligned TKA [37], and a recommended femoral sagittal alignment of within 3° exion could be acquired in only 25% of the studied cases [38]. In addition, Iorio et.al found that traditional instrumentations failed to achieve ideal tibial component positioning, with a tendency towards decreased tibial slope [39].…”
Section: Discussionmentioning
confidence: 99%
“…On the frontal plane, no patients operated on with EM guide were outside 3 degrees of alignment range, while 22% in the IM cohort had a final alignment outside 3 degrees of range. Although recent studies 13 14 questioned the role of overall TKA postoperative alignment in implant survival, most of the authors 1 2 10 15 still advocate placing the implant within 3 degrees of a neutral mechanical axis. Fang et al, 10 in their retrospective study, based on 6,070 TKA patients looking for implant survival in well-aligned knees compared with that of the outliers (more than 3 degrees of valgus or varus alignment) reported that well-aligned TKAs has a longer survival than ones placed in varus or valgus alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 3,048 knees investigated at 15.8 years, 3.3% of flexed required revision while no neutrally aligned femoral implants required revision. Maderbacher et al 2 found that IM alignment rods caused a mean sagittal alignment of the cutting block of 4.4 degrees of flexion in relation to the mechanical femoral axis. In only 25% of the observed cases, a flexion within a range of the desired value of 0 to 3 degrees was obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation